Improved Biosafety and Transdermal Delivery of Aconitine via Diethylene Glycol Monoethyl Ether-Mediated Microemulsion Assisted with Microneedles - Yongtai Zhang; Hongmei Hu; Qian Jing; Zhi Wang; Zehui He; Tong Wu; Nian-Ping Feng (MDPI AG, 2020)
In the current study, diethylene glycol monoethyl ether-mediated microemulsions were combined with microneedles for enhanced transdermal aconitine delivery. The oil-in-water microemulsion increasedaconitine solubility and enhanced transdermal drug delivery and assistance with metal microneedles enhanced permeation of the aconitine-loaded microemulsion. Carried by the microemulsion, the in vitro permeability of aconitine was significantly enhanced, and further improved using microneedles. In vivo microdialysis revealed that the subcutaneous local drug concentration reached a high level within 30 min and remained relatively consistent to the end of the experimental period. AUC0-t of the microemulsion group was significantly higher than that of the aqueous solution group, and the microemulsion combined with microneedles group achieved the highest AUC0-t among the tested groups. The microemulsion and microdialysis probe also showed good biocompatibility with skin tissue. The microemulsion could be internalized by HaCaT and CCC-ESF-1 cells via lysosomes. The in vitro cytotoxicity of aconitine toward skin cells was reduced via encapsulation by microemulsion, and the prepared microemulsion developed no skin irritation. Hence, transdermal aconitine delivery and drug biosafety were effectively improved by loading into the microemulsion and assisting with microneedles, and in vivo microdialysis technique is suitable for realtime monitoring of transdermal drug delivery with microemulsion-based drug vehicles.